Assessment of Child, Mother, and Environmental Factors Associated with Undernutrition in Children Less than Five Years Old in a Maya Community in Yucatan, Mexico - Glenn, Joelle C.; Walden, Heather S.; Guzmán-Marín, Eugenia; Gonzalez-Losa, María del Refugio; McIntosh, Antoinette; Young, Alyson G.; Hernandez, Jorge A. (International Journal of Child Health and Nutrition, 2014)
The objective of this study was to examine child, mother, and environmental factors associated with undernutrition in children less than five years old in a Maya community in Yucatan, Mexico. This investigation was designed as a case-control study. All cases (n=42) of undernutrition were included, and a sample of 52 controls was randomly selected from the study population. The frequency of investigated exposure factors was compared between cases and controls by using logistic regression. Undernutrition was associated with child’s age (> 36 months old; OR = 3.53; 95% CI = 1.04, 18.40) and mother’s marital status (married; OR = 0.29; 95% CI = 0.09, 0.90). The odds of undernutrition were 2.81 times higher in children infected with Giardia spp, but this association was not significant (P = 0.18) after controlling for child’s age and mother’s marital status. In conclusion, child’s age and mother’s marital status were associated with child undernutrition in study subjects. Futures studies on undernutrition in children should examine more carefully how mother’s marital status alone or in combination with other factors (e.g. socio-economic, psychological factors) can influence child nutrition.